2021
DOI: 10.1097/ajp.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Preference for Fatigue-avoidance Goals as a Mediator Between Pain Catastrophizing, Functional Impairment, and Walking Behavior in Women With Fibromyalgia

Abstract: Objectives: Along with the symptoms of pain and fatigue, pain catastrophizing and avoidance behaviors are highly prevalent and associated with functional impairment in fibromyalgia (FM) patients. Although pain and fatigue affect patients' quality of life, research has been exclusively focused on how pain affects physical activity and exercise. The aim of this study was to analyze the role of pain catastrophizing and preference for fatigue-avoidance goals in walking behavior and functional impairment in women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 67 publications
(162 reference statements)
0
8
0
Order By: Relevance
“…The serial multiple mediation (SMM) analyses performed confirmed this hypothesis. Following the fear-avoidance models [ 12 , 15 ], our results pointed out that pain catastrophizing beliefs stop patients from engaging in physical activity, and this increases FM impact [ 9 , 16 , 17 ]. Previous research has also shown that pain catastrophizing is related to higher levels of pain and fatigue [ 13 ].…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The serial multiple mediation (SMM) analyses performed confirmed this hypothesis. Following the fear-avoidance models [ 12 , 15 ], our results pointed out that pain catastrophizing beliefs stop patients from engaging in physical activity, and this increases FM impact [ 9 , 16 , 17 ]. Previous research has also shown that pain catastrophizing is related to higher levels of pain and fatigue [ 13 ].…”
Section: Discussionmentioning
confidence: 72%
“…Based on previous literature [ 16 , 17 ], we propose two serial multiple mediation models (SMM) defined by pain catastrophizing (M 1 ) and impact of FM (M 2 ) on pain (SMM 1 ) and fatigue after 6-MWT as outcome variables (SMM 2 ). All indirect effects were significant in both models for regular walking behavior on pain/fatigue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In women with fibromyalgia, from a motivational approach, the roles of catastrophizing and goal preferences have been explored in functional limitations. However, fatigue avoidance was one of the goal preferences relative to other achievement goals focused on several daily life tasks (work and homework) [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is often difficult to facilitate motivation for more PA in PwF when pain and related symptoms such as worrying and catastrophizing are present. 43,44 As indicated in the current review, lack of motivation to be physically active is a barrier for reducing SB. In these very complex situations where PA is less tolerated, PwF should be encouraged to at least interrupt SB by standing up regularly.…”
Section: General Findingsmentioning
confidence: 96%